Platform Session – NIBS: Developmental differences in motor cortex TMS-EEG responses associate with local white matter microstructure. (May 2018) - Kallioniemi, Elisa; Säisänen, Laura; Gröhn, Heidi; Ferreri, Florinda; Lakka, Timo; Lintu, Niina; Lindi, Virpi; Könönen, Mervi; Määttä, Sara
Abstract : Introduction: The reactivity to transcranial magnetic stimulation (TMS) changes with development. For example, motor cortex TMS-evoked EEG response decreases significantly with age. Structurally, the grey matter of the motor cortex reaches maturity by the age of 10 years, whereas the maturation of superficial white matter continues until early adulthood. The relationship between these concurrent structural and functional changes remains unclear. Methods: We studied 10 healthy children (mean age 10.5), 10 adolescents (mean age 16.0 years) and 7 adults (mean age 26.5 years). Fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD) and radial diffusivity (RD) were defined from diffusion weighted MRI data obtained from the left hand knob area on motor cortex. Cortical thickness (grey matter, GM) of the same area was assessed from T1-weighted MRI. TMS was focused on the left hand knob with a stimulation intensity of 110% of the resting motor threshold. EEG was recorded with a 60-channel TMS-compatible amplifier. The total EEG activity was assessed using the global mean field power (GMFP) calculated across all electrodes and the local activation as a local mean field power (LMFPleft ) computed across the electrodes surrounding the left hand knob. GMFP and LMFPleft areas in the 15–500 ms post stimulus interval were used for statistical analyses. Between-group differences in TMS-EEG, GM and DTI metrics were analyzed with one-way ANOVA, and Pearson's correlation was used to analyze correlations between functional and structural data. Results: GMFP area ( F  = 12.65, p  < 0.001) as well as LMFPleft ( F  = 20.19, p  < 0.001) differed between the groups, the values being largest in children and smallest in adults, as expected. AD decreased significantly with age ( F  = 7.30, p  < 0.01), while FA and MD showed trend of age dependent changes ( p  = 0.05–0.07). However, GM at the left hand knob did not differ between the age groups ( p  > 0.8). GMFP and LMFPleft showed a significant correlation with MD ( r  = 0.421, p  < 0.05 for the GMFP and r  = 0.591, p  < 0.01 for LMFPleft ) and AD ( r  = 0.555, p  < 0.01 for GMFP and r  = 0.595, p  < 0.01 for the LMFPleft ) values. GM correlated significantly with RD ( r  = 0.443, p  < 0.05) and MD ( r  = 0.411, p  < 0.05) but not with GMFP or LMFPleft . Conclusion: Previously, it has been suggested that smaller EEG responses in adults compared with those in children may be associated with GM loss in the pre- and peripubescent period. In this study, a developmental decline of TMS evoked global and local EEG responses correlated with the maturation of local short-range microstructural changes revealed by DTI rather than GM in the motor cortex. These results indicate that the development profile of TMS-evoked EEG activity may associate with maturation of the microstructure of underlying short range white matter connections.